Effect of His-Tag on Expression, Purification, and Structure of Zinc Finger Protein, ZNF191(243-368) - Dongxin Zhao; Zhongxian Huang (Bioinorganic Chemistry and Applications)
Zinc finger proteins are associated with hereditary diseases and cancers. To obtain an adequate amount of zinc finger proteins for studying their properties, structure, and functions, many protein expression systems are used. ZNF191(243-368) is a zinc finger protein and can be fused with His-tag to generate fusion proteins such as His6-ZNF191(243-368) and ZNF191(243-368)-His8. The purification of His-tag protein using Ni-NTA resin can overcome the difficulty of ZNF191(243-368) separation caused by inclusion body formation. The influences of His-tag on ZNF191(243-368) properties and structure were investigated using spectrographic techniques and hydrolase experiment. Our findings suggest that insertion of a His-tag at the N-terminal or C-terminal end of ZNF191(243-368) has different effects on the protein. Therefore, an expression system should be considered based on the properties and structure of the protein. Furthermore, the hydrolase activity of ZNF191(243-368)-His8 has provided new insights into the design of biological functional molecules.